2019
DOI: 10.1093/bib/bbz015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of integrative clustering methods for the analysis of multi-omics data

Abstract: Recent advances in sequencing, mass spectrometry and cytometry technologies have enabled researchers to collect large-scale omics data from the same set of biological samples. The joint analysis of multiple omics offers the opportunity to uncover coordinated cellular processes acting across different omic layers. In this work, we present a thorough comparison of a selection of recent integrative clustering approaches, including Bayesian (BCC and MDI) and matrix factorization approaches (iCluster, moCluster, JI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 33 publications
1
61
1
Order By: Relevance
“…We benchmarked in-depth nine jDR algorithms, representative of multi-omics integration approaches, in the context of cancer data analysis. In contrast to existing comparisons [10][11][12][13] , our benchmark not only focuses on the evaluation of the clustering outputs, but also evaluates the biological, clinical, and survival annotations of the factors and metagenes. Existing comparisons also mainly use simulated data; we here consider large datasets of bulk cancer multi-omics as well as single-cell data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We benchmarked in-depth nine jDR algorithms, representative of multi-omics integration approaches, in the context of cancer data analysis. In contrast to existing comparisons [10][11][12][13] , our benchmark not only focuses on the evaluation of the clustering outputs, but also evaluates the biological, clinical, and survival annotations of the factors and metagenes. Existing comparisons also mainly use simulated data; we here consider large datasets of bulk cancer multi-omics as well as single-cell data.…”
Section: Discussionmentioning
confidence: 99%
“…Dimensionality Reduction (DR) approaches decompose the omics into a shared low-dimensional latent space 8,9 . Four recent reviews tested and discussed some of these existing methods from the clustering performance perspective [10][11][12][13] . Pierre-Jean et al 12 , Rappoport et al 10 and Tini et al 13 selected one method from each of the aforementioned three categories, while Chauvel et al 11 focused on Bayesian and DR approaches.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…49,50 CyTOF can also work in conjunction with other techniques including single-cell genome and transcriptome profiling 169,170 and bioinformatic pipelines. 171,172 For instance, Zheng et al conducted CyTOF profiling of immune microenvironment in hepatocellular carcinoma and revealed that leading-edge regions exhibited an increase of tumor-associated CD4/CD8 double-positive T (DPT) cells, which synergistically expressed PD-1/HLA-DR/ICOS/CD45RO. 173 Single-cell RNA-seq was employed to characterize DPT cells and specifically identified PD-1 high DPT cluster derived from intratumoral CD8 + T cells.…”
Section: Perspectivementioning
confidence: 99%
“…In this review, we focus on the cross-domain relation inference (or link prediction) problem for the HMLN. Readers can refer other excellent reviews of the multiplex networks (Chauvel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%